Processo de planejamento estratégico em universidade pública: o caso da Universidade Federal do Pará - Athanázio, Madeleine Mônica (2010)
The goal of this research is to check if the strategic planning developed between 2001 and 2009 into the State University of Para (Universidade Federal do Pará - UFPA) was consolidated into its Academic Centers as a management practice. To this end, we identified the planning formalization degree of the Academic Centers, the conceived tools for the planning, the conception and the methodological process used in the tools elaboration, as also its implementation. The research used a qualitative approach: it is descriptive and it uses the case study technique. The data were gathered from primary and secondary sources, through bibliography, documents, and field researches through semi-structure interviews. The analysis and data interpretation were done by each investigated Academic Center from the analytics categories guided by the specifics goals. We used theoretic fundamental based principles and the university as a study empiric reference based on its structure analysis, organizational processes and institutional strategic plan. We inspected how the strategic planning process was developed throughout the fixed period and how the investigated Academic Centers are from the collected documents and interviews. The theoretical foundation was built from three axis: the Brazilian undergraduate and posgraduate education system; the university itself including its singularity and complexity as an organization; and the planning as a strategic management process. The main results show us that the UFPA has updated regulatory milestones, presenting organizational structure, laws, instructions, manuals and deployed management model that give the strategic planning development conditions beyond its administration, i. e., into its Academic Centers. The centers also present those established milestones and develop the basic planning processes of the institution. Those processes are conceived based on the institutional strategic planning and the managers mainly use the procedural orientation defined by the university management, from where the conceptual foundation is originated and propagated. According to the literature and to the research done in this work, we can conclude that the Academic Centers from the UFPA developed the strategic planning practice. This planning is organized and founded and guided the plans and decisions which avoided the disordered management and, according to the managers, allowed the advances and performance improvement. We can conclude that the UFPA built an important foundation with respect to the management professionalization. On the other hand, we can not conclude that the management practice is consolidated since there are weaknesses into the structuring of the technical teams and there is not any management tool for the implementation of the elaborated plans